2021
DOI: 10.1002/qre.2929
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method based on P and P′ control chart for identifying hotspots

Abstract: The terms “hotspots,” “blackspot,” or “high‐risk” are normally used for an area on a road where the number of car accidents are far beyond the normal level and, more importantly, the causes of the incident always link to one or many specific reasons. Identifying these spots is helpful and may assist people in authority to implement corrective actions. To do the aforementioned, some decision‐support tools could be useful since they enable us to monitor the indicators that may lead to a car accident, same as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Sci. 2024, 14,2108 This experiment requires the use of street view image semantic segmentati the corresponding road intersection data. There are 2519 intersections in intersections are mainly divided into two categories: one is traffic black spot i and the other is non-traffic black spot intersections.…”
Section: Selection Of Training Objective Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. 2024, 14,2108 This experiment requires the use of street view image semantic segmentati the corresponding road intersection data. There are 2519 intersections in intersections are mainly divided into two categories: one is traffic black spot i and the other is non-traffic black spot intersections.…”
Section: Selection Of Training Objective Functionmentioning
confidence: 99%
“…The emergence of geographic big data and the rapid development of machine learning and deep learning make it possible to portray the built environment of urban roads from street view image data [11][12][13]. In real life, traffic accidents are also more likely to occur on densely populated streets with crowded and dilapidated buildings, without better road infrastructure, and with missing road markings and blurred and uneven road surfaces [14][15][16]. These features are all part of the built environment of urban roads, which can be described by street image data.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that it was beneficial to divide the accident site by using the heat map analysis method of kernel density estimation. Jahan et al [17] developed a hybrid method, based on accident type, for improving the rate quality control method to overcome the shortcomings. According to the case study and based on the results in the real environment, the proposed method could detect and identify the accident hotspots.…”
Section: Introductionmentioning
confidence: 99%